2015
DOI: 10.1080/15592324.2014.1003755
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ubiquitin ligase HOS1 is involved in ethylene regulation of leaf expansion inArabidopsis

Abstract: Ethylene regulates a variety of physiological processes, such as flowering, senescence, abscission, and fruit ripening. In particular, leaf expansion is also controlled by ethylene in Arabidopsis. Exogenous treatment with ethylene inhibits leaf expansion, and consistently, ethylene insensitive mutants show increased leaf area. Here, we report that the RING finger-containing E3 ubiquitin ligase HIGH EXPRESSION OF OSMOTICALLY RESPONSIVE GENES 1 (HOS1) regulates leaf expansion in an ethylene signaling pathway. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…8d). This SNP is predicted to be an E3-ubiquitin ligase (He et al, 2013), which is involved in the regulation of ET action by targeting ubiquitination of ACS proteins, particularly types 2 and 3 (Lee & Seo, 2015). Of the 873 E3-ligase genes identified so far in wheat, 173 genes are expressed differentially during grain development (Capron et al, 2012).…”
Section: Researchmentioning
confidence: 99%
“…8d). This SNP is predicted to be an E3-ubiquitin ligase (He et al, 2013), which is involved in the regulation of ET action by targeting ubiquitination of ACS proteins, particularly types 2 and 3 (Lee & Seo, 2015). Of the 873 E3-ligase genes identified so far in wheat, 173 genes are expressed differentially during grain development (Capron et al, 2012).…”
Section: Researchmentioning
confidence: 99%
“…E3-ubiquitin-ligases-mediated ubiquitination are emerging as major regulators in plants’ response to abiotic stress, circadian rhythm control, cell cycling and plant-microbe interactions [29,30,31]. High expression of osmotically responsive genes1 (HOS1), one of the RING finger-containing E3 ubiquitin ligase, was initially described as a cold-signaling attenuator of ICE1 [9,32], and also involved in ethylene signal transduction [33] and photoperiodic flowering [34] in Arabidopsis . It is reported that most of the plant species just have a single copy of the HOS1 gene [35], suggesting that HOS1 would have important roles in various plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been suggested that HOS1 is also involved in ethylene and auxins responses. 18,19 Therefore, a cross-talk between the HOS1 associated processes and different plant hormones is expected.…”
Section: High Expression Of Osmotically Responsive Gene 1 (Hos1)mentioning
confidence: 99%